INTERNALISASI SPIRITUAL QUOTIENT (SQ) DALAM TRADISI KOLOMAN SAMMAN (Studi Fenomenologi agama di Dusun Sobih Keluruhan Bugih Pamekasan) - Ramadhan, Yusfar (El-Waroqoh : Jurnal Ushuluddin dan Filsafat, 2025)
Culture is an important element in human life, so it attracts attention from various fields of science such as sociology and anthropology. One of the local traditions in Madura, especially the Sobih Bugih Pamekasan area, which is still preserved today is Koloman Samman. The Samman column tradition is a tradition of community gatherings by reading dhikr and poetry containing praise to Allah SWT. Apart from containing religious elements in it, the Samman column also contains high social elements. Community friendship will be maintained, thereby minimizing feuds and increasing solidarity among others. The theory used is a qualitative approach. A qualitative approach with a type of phenomenology is used to capture and understand how the spiritual quotient is internalized through the Samman column tradition and find the meaning implicit in it. The data sources for this research are divided into two sources, namely primary and secondary data sources. The main source of information is the reporter who conducted interviews, observations and documentation required by the researcher. Meanwhile, the secondary data source is data taken from non-participant communities in the Samman column activity. Based on the results of analysis related to the research carried out , regarding the Koloman Samman Tradition: A Form of Internalization of the Spiritual Quotient (Sq) (Phenominological Study of Sobih Hamlet, Bugih District Pamekasan) it can be concluded as follows: Internalization of Islamic values in community life can be realized in the Samman column, with several notes, that internalization Religious values in the character of society requires a long process